The effect of group prenatal care for women with diabetes on social support and depressive symptoms: a pilot randomized trial. (2nd May 2020) - Mazzoni, Sara; Hill, Pamela; Briggs, Ariel; Barbier, Kate; Cahill, Alison; Macones, George; Colditz, Graham; Tuuli, Methodius; Carter, Ebony
Abstract: Objective: To measure the impact of group prenatal care (GPC) on diabetes-specific peer support and depressive symptoms in women with pregnancies complicated by diabetes. Materials and methods: This is a planned secondary analysis of a two-center pilot randomized controlled trial conducted at Denver health (DH) and Washington University in St. Louis (WU) including Spanish (DH) or English (WU) speaking women with type 2 or gestational diabetes. Women were randomized to diabetes GPC or individual prenatal care (IPC) in the resident diabetes clinic. Participants completed an Edinburgh Postnatal Depression Scale (EPDS) at randomization, at 38-week gestation and at 6–12 weeks postpartum. The diabetes support scale (DSS), which includes 12 questions answered on a Likert scale, was administered at 38 weeks. Analysis was by intention to treat (clincaltrials.gov#NCT02444325). Results: A total of 84 women were consented and randomized. Six withdrew consent (two from each cohort) or were lost to follow-up (two from IPC), and three did not complete the 38-week assessment (two from GPC and one from IPC), resulting in primary outcome data available for 75 women: 38 in GPC and 37 in IPC. More women randomized to GPC reported composite positive peer support on the DSS (52.5 versus 26.3%; p < .02). There were no differences in EPDS scores, depression (EPDS >10), or rates of improved EPDS score from baseline to 38 weeks. Conclusion: GPC for women with diabetes is associated with improved diabetes-specific peer social support with no significant impact on depressive symptoms. Clinical trial registration: Clincaltrials.gov NCT02444